Practical formalism: A new methodological proposal for business ethics - Brady, F. Neil (Journal of business ethics, 1988)
The traditional exposition of Kantian ethical theory in the business ethics literature is abstract, esoteric, and impractical compared to the more usable presentations of utilitarianism. This situation can be improved by identifying and describing the conceptual dimensions of formalistic ethical reasoning, as contained in the interplay between case and principle, with examples from the business/society literature.